Efficient multicasting technique for elastic optical network. Issue 1 (22nd December 2020) - Tarhani, Mehdi; Sarkar, Sanjib; Eghbal, Morad Khosravi; Shadaram, Mehdi
Abstract: The elastic optical network (EON) is the latest solution to increase the capacity of optical networks, as a response to the ever‐increasing demand for traffic. To meet the EON mission, new algorithms and frameworks need to be designed. In this paper, a new algorithm based on EON is proposed that employs a subtree‐based scheme to establish multicast transmissions. To solve the problems of routing, modulation level and spectrum allocation, the primary problem of EON with regard to resource allocation under wavelength continuity and wavelength contiguity constraints, as well as distance adaptive transmission, the proposed algorithm solves each subproblem by considering the existence of a solution for other subproblems. The authors take into account the effects of splitting the transient light at the intermediary nodes on the signal‐to‐noise ratio to enhance the accuracy of the resource allocation. The proposed scheme is extensively examined under different networks and compared with the existing multicasting benchmark. The simulation results show that the proposed scheme considerably increases the network capacity without placing any burden on the network.